Using patient-reported outcome measures (PROMs) to promote quality of care in the management of patients with established kidney disease requiring treatment with haemodialysis in the UK (PROM-HD): a qualitative study protocol. Issue 10 (28th October 2018) - Anderson, Nicola Elzabeth; Calvert, Melanie; Cockwell, Paul; Dutton, Mary; Aiyegbusi, Olalekan Lee; Kyte, Derek
Abstract : Introduction: Patients undergoing haemodialysis (HD) for end-stage kidney disease often report a poor quality of life (QoL) and identify that improving QoL has a higher priority for them than improvements in long-term survival. Research suggests that regular collection and usage of patient-reported outcome measures (PROMs) in patients with chronic conditions may reduce hospitalisation, improve QoL and overall survival. In the UK, despite increased use within research settings, PROMs have not been introduced into the routine clinical care for patients undergoing HD. We report the protocol for 'Using patient reported outcome measures (PROMs) to promote quality of care in the management of patients with established kidney disease requiring treatment with haemodialysis in the UK—PROM-HD'. The study aim is to investigate the methodological basis for the use of routine PROMs assessment, particularly using electronic formats (ePROMs) within clinical and research settings, to maximise the potential of PROM use in the management of the care of this patient group. Methods and analysis: The project will use qualitative methodology to explore, by thematic analysis, the views, perceptions and experiences of patients receiving HD and members of the HD multidisciplinary team regarding the collection and use of PROMs in routine clinical care, particularly ePROMs. This will involve interviews with up to 30 patients or until saturation is achieved and three focus group sessions with approximately 18 members of the clinical team delivering care to this patient group, which will be interpreted broadly to include both professional and non-professional staff.